Long-term survival of bryophytes underground: an investigation of the diaspore bank of Physcomitrium eurystomum Sendtn. (3rd July 2022) - Callaghan, Des A.; During, Heinjo; Medina, Rafael; Yang, Handong
ABSTRACT: Introduction: Bryophyte diaspore banks are a critical aspect of the life strategy of some species yet remain neglected and poorly understood. This study investigated the longevity in natural habitat of the diaspore bank of Physcomitrium eurystomum Sendtn., a moss species that is threatened with extinction in Europe. Methods: Undisturbed soil cores of 40 cm depth were collected from Langmere, Norfolk, UK, and were split into investigated sediment layers of 1 cm depth. Dating of sediment layers was done by an analysis of radionuclides, and diaspore germination trials of each layer were carried out in a growth chamber. DNA barcoding was used to help identify plants that germinated. Key results and conclusions: Viable diaspores of Physcomitrium eurystomum frequently occurred in sediment layers that were at least 100 years old and continued to occur in much lower layers that were probably several hundred years old. The long-term survival of bryophytes underground can have important implications for conservation decisions.